Andung-Andung Mate di Ranto - Rosmegawaty Tindaon; GR Lono Lastoro Simatupang; Victor Ganap; Timbul Haryono (Resital: Jurnal Seni Pertunjukan (Journal of Performing Arts), 2018)
This study aims to understand the song of Mate di Ranto from a musicological perspective. The main data of this research is the song of Mate di Ranto by Poster Sihotang. The analysis was done by observing the melody and the lyrics of the song. Based on the research it is concluded that the song of Mate di Ranto is a song of Toba people with the genre of andung-andung, which is a melancholic nuance and has a meaning as an expression of sadness. This song is inspired by the andung-andung of death ceremony. This song is the result of a blend of traditional singing style of andung-andung and popular music singing styles. This song uses a combo band accompaniment which is composed by combining elements of pop music and traditional Toba music.